Primary renal sporadic hemangioblastoma: A case report and literature review - Zhang, Jun; Wang, Ning; Chen, Li-Hong; Wang, Wen-Juan; Wang, Mingwen; Liu, Hao; Jiang, Han-Guo; Qi, Yan (Frontiers in Urology, 2022)
Sporadic renal hemangioblastomas (RHBs) are a rare subgroup of extraneurologic hemangioblastomas. They are under-recognized renal tumours whose differential diagnosis remains challenging. Here, we describe a case of RHB in a 61-year-old man was admitted to the hospital two days after the discovery of a right kidney mass. Renal carcinoma was clinically considered, and a radical nephrectomy was performed. Follow-up showed no evidence of postoperative tumour recurrence. Histologically, the tumour boundary is clear and fibrous envelope is visible. The tumour issue was mainly composed of tumour cells and a dendritic capillary network, which consisted of multicellular and oligocellular areas. The tumour cells were polygonal, the cytoplasm was eosinophilic or transparent, and intranuclear pseudoinclusions were found. Immunohistochemically, vimentin, a-inhibin, neurogenic specific enolase (NSE), S-100, smooth muscle actin (SMA), and cluster of differentiation (CD)10 antibodies reacted strongly and were diffused, and Ki-67 was 2% positive. CD31 and CD34 showed vascular morphology. We also summarized related case reports (a total of 41 cases in the Chinese and English literature) to explore the clinicopathological characteristics of RHB and improve the diagnosis and treatment of this disease. RHB is a benign tumour with excellent prognosis; however, it is easily misdiagnosed as other common renal malignancies. Immunohistochemistry is vastly helpful in accurate diagnosis of RHB. Preoperative renal biopsy can effectively avoid misdiagnosis and overtreatment.